Integrating Risk Management and Absorptive Capacity: Enhancing Business Performance in Micro, Small, and Medium Enterprises (MSMEs) in the Food and Beverage Sector - Syahyono, Syahyono; S. Syahyono (Coopetition : Jurnal Ilmiah Manajemen, 2025)
This study examines the interplay between risk management and absorptive capacity in improving business performance for Micro, Small, and Medium Enterprises (MSMEs) in the Food and Beverage (F&B) sector. MSMEs face increasing challenges due to globalization, market uncertainties, and technological changes, making risk management and absorptive capacity crucial for sustaining competitive advantage. The research investigates how effective risk management strategies, combined with a strong absorptive capacity, can enhance MSMEs’ financial and operational performance. By employing a quantitative approach and Structural Equation Modeling (SEM), data from 650 F&B MSMEs in West Java, Indonesia, were analyzed. The findings reveal that risk management significantly influences absorptive capacity, which in turn positively impacts business performance. This study highlights the importance of integrating these two factors, with absorptive capacity serving as a key mediator between risk management and business performance. Practical recommendations for MSMEs include strengthening risk management frameworks and fostering employee engagement to enhance absorptive capacity, thereby improving business outcomes. The results provide valuable insights for MSME owners and managers on how to navigate uncertainties and leverage knowledge to improve sustainability and competitiveness in a dynamic market environment.